(untitled) (Journal of Laboratory Animal Science, 2024)
The article summarises the outcomes of an international conference of Laboratory Animal Scientists’ Association (LASA, India) on “Advancements of 3Rs in Biomedical Research, Laboratory Animal Science and Welfare: International Perspectives” which was organised by the Conference Committee and Organising Secretary, Dr. R K Shakthi Devan, Syngene International Ltd, Bangalore; Secretary, Laboratory Animal Scientists’ Association; and Indian College of Laboratory Animal Medicine at National Science Seminar Complex, JN Tata Auditorium, Indian Institute of Science, Bangalore on 7 and 8 November 2023 and preconference workshops also held on 6 November 2023. LASA India is a national organization dedicated to advancing laboratory animal science by promoting the ethical care and use of laboratory animals. LASA has more than 1000 life members from biomedical professionals including Veterinarians, Scientists, Academicians, Researchers, Technical experts from industry, state and central institutions in the field of laboratory animal science. The organisers felt a need for the promotion of 3R’s (Replacement, Reduction and Refinement) through this international event which was planned meticulously.